Participatory rapid appraisal for community development : - Theis, Joachim (Funded by the Ford Foundation, 1991)
This training manual is divided two main sections. The first section gives some guidelines on how to organize ana prepare a training course in participatory appraisal. The second section describes in details individual training sessions, including guidelines on how to help a PRA team put the tools they have learn into use. Each session includes examples and practice exercises.